2008
DOI: 10.1002/eji.200738051
|View full text |Cite
|
Sign up to set email alerts
|

IL‐12, IL‐23, and IL‐27 enhance human β‐defensin‐2 production in human keratinocytes

Abstract: IL-12, IL-23, and IL-27, which are produced by APC, modulate innate and adaptive immunities. Human b-defensin-2 (hBD-2) produced by epidermal keratinocytes promotes cutaneous antimicrobial defense and inflammation. We examined the in vitro effects of IL-12, IL-23, and IL-27 on hBD-2 production in human keratinocytes. IL-12, IL-23, and IL-27 enhanced IL-1b-induced hBD-2 secretion and mRNA expression in keratinocytes. The stimulatory effects of IL-12, IL-23, and IL-27 were suppressed by antisense oligonucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 47 publications
4
49
0
Order By: Relevance
“…IL-27 also activates the transcription factors STAT1, STAT3, and STAT6. STAT1 and STAT3 activation by IL-27 has been shown in other studies in T cells, monocytes, and keratinocytes (22,23). However, this is the first study reporting phosphorylation of STAT6 by IL-27.…”
Section: Discussionsupporting
confidence: 67%
“…IL-27 also activates the transcription factors STAT1, STAT3, and STAT6. STAT1 and STAT3 activation by IL-27 has been shown in other studies in T cells, monocytes, and keratinocytes (22,23). However, this is the first study reporting phosphorylation of STAT6 by IL-27.…”
Section: Discussionsupporting
confidence: 67%
“…IL-23 secreted by skin dendritic cells induces the production of IL-17 and IL-22 by Th17 cells. These mediators will act on keratinocytes leading to their activation and hyperproliferation, which then recruit and activate immune cells in the inflamed skin [20] . Furthermore, Zaba et al [21] showed that anti-TNF-α agents are able to modulate IL-23p19 and IL-12p40 mRNA levels as well as the inflammatory infiltration in the psoriatic skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides microorganisms, LTB4, L12, L23, L27 and certain other immune factors also induce the expression of hBD-2 (24,28). However, using these microorganisms to study the regulation and function in vivo and in vitro often leads to the threat of a biological hazard.…”
Section: Discussionmentioning
confidence: 99%